The Effects of Ethanolic Extract of Handal (Citrullus colocynthis L.) Fruit Pulp on Blood Glucose level in Normal Fasting Rats - Babiker, Hanaa A.; Taj Eldin, Imad M.; M, Abd Elwahab H. (Gezira Journal of Health Sciences, 2012)
Background: Citrullus colocynthis L. is a member of the family Cucurbitaceae. It is widely available in Sudan and traditionally used for treatment of skin infections, diabetes and constipation worldwide. Objectives : This study aimed to investigate the effects of ethanolic extract of C. colocynthis fruit pulp on blood glucose level in normal fasting rats. Method: Two groups of rats, each of twenty one were used to study the effects of the extract (300 mg/kg/ml) on fasting blood glucose level (BGL) and glucose tolerance test (GTT). Results: The oral administration of ethanolic extract of C. colocynthis fruit pulp resulted in a sudden drop in BGL of normal fasting rats after four hours. This was accompanied by some toxic effects appeared as severe diarrhea, followed by deaths of some rats (2/7). Moreover, the administration of the extract did not exhibit a remarkable reduction or improvement in the induced hyperglycemia.   Conclusion: This study showed that, ethanolic extract of C. colocynthis fruit pulp reduced the BGL without significant hypoglycemic effect and the extract appeared to be highly toxic..